2012
DOI: 10.1051/0004-6361/201118383
|View full text |Cite
|
Sign up to set email alerts
|

A peculiar Of star in the Local Group galaxy IC 1613

Abstract: Context.Results from the theory of radiatively driven winds are nowadays incorporated in stellar evolutionary and population synthesis models, and are used in our interpretation of the observations of the deep Universe. Yet, the theory has been confirmed only until Small Magellanic Cloud metallicities. Observations and analyses of O-stars at lower metallicities are difficult, but much needed to prove the theory. Aims. We have observed GHV-62024, an O6.5 IIIf star in the low-metallicity galaxy IC 1613 (Z ≈ 0.15… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 46 publications
(84 reference statements)
4
39
0
Order By: Relevance
“…Tramper et al (2011) report six stars with stronger wind momentum than expected from the poor metallicity of their host galaxies (∼1/7 Z ) from X-Shooter spectroscopic analyses, although error bars are too large for results to be determinant. Our analysis of an Of star in IC 1613 (Herrero et al 2012) concluded that the star may have a strong wind or, alternatively, a slower than expected wind acceleration. Lucy (2012) argues that the neglect of wind clumping may explain these findings, but also suggests that the discrepancy may be caused by an additional wind-driving mechanism operating only at certain metallicities, temperatures and luminosities, or negligible in the Galactic counterparts.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Tramper et al (2011) report six stars with stronger wind momentum than expected from the poor metallicity of their host galaxies (∼1/7 Z ) from X-Shooter spectroscopic analyses, although error bars are too large for results to be determinant. Our analysis of an Of star in IC 1613 (Herrero et al 2012) concluded that the star may have a strong wind or, alternatively, a slower than expected wind acceleration. Lucy (2012) argues that the neglect of wind clumping may explain these findings, but also suggests that the discrepancy may be caused by an additional wind-driving mechanism operating only at certain metallicities, temperatures and luminosities, or negligible in the Galactic counterparts.…”
Section: Introductionmentioning
confidence: 71%
“…7. It includes all O-type stars in IC 1613 whose effective temperature has been derived from quantitative spectroscopic analysis: the eight stars analysed in this paper, plus five stars from Tramper et al (2011) and Herrero et al (2012). For comparison, we have added temperature determinations of SMC OB-stars from Mokiem et al (2007) and Massey et al (2009), and the temperature scale for SMC B-supergiants derived by Trundle et al (2007).…”
Section: The Very Low-metallicity Temperature Scalementioning
confidence: 99%
See 3 more Smart Citations